The Fat Content and Organoleptic Value of Broiler Eggs Soaked in Bay Leaf Infusion (Eugenia polyantha)): - - Suryono, Suryono; Sestilawarti, Sestilawarti (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2021)
Chicken eggs are animal foods that are consumed by many people because they are cheaper and easier to obtain than other animal foods. Bay leaf is known to the public as one of the most popular kitchen spices not only because of its many health benefits, but also because of its attractive organoleptic quality (aroma). Eggs soaked in bay leaf infusion are also expected to produce attractive organoleptic qualities without affecting their chemical quality (fat content). The research design used was a 4 x 4 factorial randomized block design (RAK) with 4 replications. Factor I is the concentration of bay leaf infusion (4 concentrations) and factor II is the immersion time (4 times). Parameters observed included chemical quality (fat content) and organoleptic quality (color, aroma, texture, taste). The data were analyzed by means of variance and if it had a significant effect, it was continued with the Duncan's Distance Test. All treatments have not been able to significantly affect the fat content of eggs. The quality value produced is still in the range of fresh egg quality. The longer the immersion the lower the organoleptic value. This research still needs to be developed so that the egg quality is increasing, especially the organoleptic quality. Keywords: broiler eggs, bay leaf infusion, soaking time, fat content, and value organoleptic.